2001
DOI: 10.1038/sj.bjp.0703974
|View full text |Cite
|
Sign up to set email alerts
|

Direct inhibitory effect of digitalis on progesterone release from rat granulosa cells

Abstract: 1 Digoxin (10 77 ± 10 75 M) or digitoxin (10 77 ± 10 75 M) decreased the basal and human chorionic gonadotropin (hCG)-stimulated release of progesterone from rat granulosa cells. 2 Digoxin (10 75 M) or digitoxin (10 75 M) attenuated the stimulatory eects of forskolin and 8-bromo-cyclic 3' : 5'-adenosine monophosphate (8-Br-cAMP) on progesterone release from rat granulosa cells. 3 Digoxin (10 75 M) or digitoxin (10 75 M) inhibited cytochrome P450 side chain cleavage enzyme (cytochrome P450 scc ) activity (conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…Ouabain (an inhibitor of Na þ /K þ -ATPase) and other digitalis glycosides induced a potentiated effect on vasoconstrictors in vitro (Fleming, 1980;Lang and Blaustein, 1980), probably in part via intracellular accumulation of calcium ions after Na þ /K þ -ATPase inhibition as occurs in myocardium (Hougen and Smith, 1978). The inhibitory effects of digoxin on the production of gonadal hormones, such as testosterone and progesterone, have been demonstrated in rat testicular interstitial cells and granulosa cells Chen et al, 2001).…”
mentioning
confidence: 96%
“…Ouabain (an inhibitor of Na þ /K þ -ATPase) and other digitalis glycosides induced a potentiated effect on vasoconstrictors in vitro (Fleming, 1980;Lang and Blaustein, 1980), probably in part via intracellular accumulation of calcium ions after Na þ /K þ -ATPase inhibition as occurs in myocardium (Hougen and Smith, 1978). The inhibitory effects of digoxin on the production of gonadal hormones, such as testosterone and progesterone, have been demonstrated in rat testicular interstitial cells and granulosa cells Chen et al, 2001).…”
mentioning
confidence: 96%
“…It has been well known that digitalis glycosides produce a positive inotropic effect on cardiac muscle through an inhibition of the Na + /K + -ATPase and an elevation of intracellular calcium concentration [2]. Previous studies demonstrated that digoxin can directly inhibit the biosynthesis of testosterone, progesterone, or corticosterone by testicular interstitial cells, granulosa cells, or adrenal zona fasciculata-reticularis cells in rats, whereas ouabain (a selective inhibitor of Na + /K + -ATPase) cannot produce any effects [7,10,11]. In the same manner, ouabain did not affect aldosterone and cortisol secretion of monkeys in the present experiment.…”
Section: Discussionmentioning
confidence: 98%
“…Digoxin inhibits the production of testosterone through a decrease in adenosine 3′:5′-cyclic monophosphate (cyclic AMP) in rat testicular interstitial cells [7,8]. In addition, digoxin decreased progesterone release by rat granulosa cells involving the inhibition of postcyclic AMP pathway, cytochrome P450 side-chain cleavage enzyme, and steroidogenic acute regulatory protein functions [9,10]. Wang et al [11] also found that digoxin decreased the release of corticosterone by rat zona fasciculata-reticularis cells involving the inhibition of the activities of adenylyl cyclase, cytochrome P450 side-chain cleavage enzyme, and 11β-hydroxylase, as well as the functions of cyclic AMP and intracellular calcium [11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been well established that hCG increases cyclic AMP generation and then stimulates progesterone secretion in granulosa cells. 19,25,26,33 Some studies have shown that LH or hCG acts via its G protein-coupled receptor to increase intracellular cAMP further to activate the PKA pathway. 33,34 In the present study, we showed that ABM-Bu decreased not only 8-Br-cAMP-or forskolin-induced progesterone release but also hCG-induced cellular cAMP production.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] The granulosa cells (2 Â 10 6 cells) were incubated with medium containing ABM-Bu (0, 100 mg/ml), ABM-Bu-G (0, 100 mg/ml) or hCG (0.5 IU/ml) for 2 h. At the end of incubation, cells were washed twice with ice-cold saline and detached by trypsinization (1.25 mg/ml). The cells were collected and extracted in homogenization buffer (pH 8.0) containing 1.5% Na-lauroylsarcosine, 1 Â 10 À3 M EDTA, 2.5 Â 10 À3 M Tris-base, 0.68% PMSF and 2% proteinase inhibitor cocktail, and then disrupted by ultrasonic sonicator in an icebath.…”
Section: Gel Electrophoresis and Western Blottingmentioning
confidence: 99%